Dual Acid‐Responsive Micelle‐Forming Anticancer Polymers as New Anticancer Therapeutics. (19th July 2013) - Kim, Byungkuk; Lee, Eunsun; Kim, Yerang; Park, Sanga; Khang, Gilson; Lee, Dongwon
<x xml:space="preserve">Abstract</x> Cinnamaldehyde, a major active compound of cinnamon, is known to induce apoptotic cell death in numerous human cancer cells. Here, dual acid‐responsive polymeric micelle‐forming cinnamaldehyde prodrugs, poly[(3‐phenylprop‐2‐ene‐1, 1‐diyl)bis(oxy)bis(ethane‐2, 1‐diyl)diacrylate]‐co‐4, 4'(trimethylene dipiperidine)‐co‐poly(ethylene glycol), termed PCAE copolymers, are reported. PCAE is designed to incorporate cinnamaldehyde via acid‐cleavable acetal linkages in its pH‐sensitive hydrophobic backbone and self assemble to form stable micelles which can encapsulate camptothecin (CPT). PCAE self assembles to form micelles which release CPT and cinnamaldehyde in pH‐dependent manners. PCAE micelles induce apoptotic cell death through the generation of intracellular reactive oxygen species (ROS) and exert synergistic anticancer effects with a payload of CPT in vitro and in vivo model of SW620 human colon tumor‐bearing mice. It is anticipated that dual acid‐sensitive micelle‐forming PCAE with intrinsic anticancer activities has enormous potential as novel anticancer therapeutics.